ENHANCING THERMAL AND COMBUSTION PERFORMANCE OF GAS WATER TANK GEYSER THROUGH BAFFLE INTEGRATION - Faiq Said; Afzal Khan; Zeeshan Khan (Spectrum of Engineering Sciences, 2025)
Enhancing the thermal and combustion performance of gas water tank geysers is crucial for improving energy efficiency and minimizing fuel consumption. This study systematically investigates the impact of seven distinct baffle configurations baseline (no baffle), strip, cylindrical, conical, finned conical, frustum, and bladed frustum on the thermal and combustion performance of a gas water tank geyser. Experimental findings demonstrate that structured baffle designs significantly enhance heat transfer, optimize fuel-air mixing, and reduce fuel consumption. Among the tested configurations, the bladed frustum baffle exhibited the highest thermal efficiency (69.03%), surpassing the conical baffle (61.24%) by 7.79% while achieving an 8.4% reduction in gas consumption. The frustum baffle demonstrated a 5.83% increase in thermal efficiency (67.07%) and a 6.49% reduction in gas consumption compared to the conical baffle, underscoring its superior heat retention and transfer capabilities. In terms of combustion performance, the frustum baffle achieved a 3.99% higher combustion efficiency (69%) than the conical baffle (65.01%), ensuring more complete fuel utilization. However, the bladed frustum baffle showed a 0.61% decline in combustion efficiency (64.4%), attributed to increased stack temperature and altered combustion dynamics. Overall, the frustum baffle emerges as the optimal configuration, offering the best balance between improved thermal efficiency (67.07%), stable combustion (69%), and reduced fuel consumption. These findings provide a robust framework for enhancing the energy efficiency of gas-fired heating systems in residential applications.